Makna Kata الإفك dan Derivasinya dalam al-Qur’an (Kajian Semantik Leksikal) - Baiq Raudatussolihah (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2021)
This study is on title The meaning Vocabulary of ifk and its derivation in the Qur'an (Semantic Lecsycal Analysis), with the formulation of the problem as follows: 1) What are the forms of vocabulary ifk and its derivation in the Qur'an, 2) How does the lexical meaning of the vocabulary ifk and its derivation in the Qur'an. This study aims to find out the ifk and its derivation vocabularies in the Qur’an. This study employs qualitative methodology by using library research approach. The collected data were processed using qualitative research method, while the data analysis and interpretation technique used was descriptive analysis-semantics. This tehchnique means that the literal meaning of each word in the Qur’an was used to interpret the verses using general semantic theory of interpretation. The words being analysed were the meaning of ifk vocabularies and its derivation di the Qur’an. The word الافك is repeated for 30 times where the word is mentioned 14 times in the form of ism, once in the form of fi’il ma’di’, and 15 times in the form of fi’il mudari. the word الإفك is interpreted as to rump up, to lie, to fool, and to warp. The Qur'an uses the words الإفك and other similar terms to show various meanings such ‘false words’ or falsehood, ‘the destruction’ of the country, ‘far’ from the truth, and ‘lies’ of the disbelievers and hypocrites. The discussion of semantic-lexical studies is certainly broad, especially when the Qur'an is made as the object of the study. Therefore this research is expected to be a reference for other researchers, especially those who are working in the field of Arabic. Therefor, the Arabic works could be further studied and being the object of research. In addition, this research is expected to have a contribution in the development of science, particularly in a semantic-lexical field of linguistic.